Determination of organochlorine compounds in the starry sturgeon (Acipenser stellatus) in different áreas of the Caspian Sea - Bakhshalizadeh , S; Nasibulina, B; Kurochkina, T; Ali, A; Mora-Medina, R; Ayala-Soldado, N (Journal of the Hellenic Veterinary Medical Society, 2025)
Nowadays, the presence of organochlorine pesticides in aquatic ecosystems is one of the main environmental concerns, due to the persistent, bioaccumulative and toxic nature of these compounds. In the Caspian Sea, the largest inland body of water in the world, there is a unique ecosystem, which is inhabited by extremely valuable species, like sturgeons. In view of that preoccupation for the aforementioned pesticides, and the critical state of the sturgeon population, our aim in this work was to evaluate their concentration in those animals throughout the Caspian Sea. For this purpose, a total of 40 adult starry sturgeons was obtained within a repopulation programme in the northern and southern coastal waters of this sea. First, the marginal pectoral fin was extracted from them, and then they were set free. The samples from each area were analysed together, and the concentration of several pesticides was ascertained. The latter were lower than the quantification limit for most of the organochlorine compounds evaluated in the different regions investigated. However, it was possible to quantify aldrin, epoxyheptachlor, heptachlor, D.D.E and dieldrin. Given the scant fat content in the study matrix, the detection of some organochlorine substances above the quantification limit in the samples obtained in this work was a reason for concern. That is why we recommend going on evaluating and adopting measures to alleviate organochlorine pollution in this region.